2021
DOI: 10.1155/2021/6641128
|View full text |Cite
|
Sign up to set email alerts
|

Multitargeted Effects of Vitexin and Isovitexin on Diabetes Mellitus and Its Complications

Abstract: Background. Till date, there is no known antidote to cure diabetes mellitus despite the discovery and development of diverse pharmacotherapeutic agents many years ago. Technological advancement in natural product chemistry has led to the isolation of analogs of vitexin and isovitexin found in diverse bioresources. These compounds have been extensively studied to explore their pharmacological relevance in diabetes mellitus. Aim of the Study. The present review was to compile results from in vitro and in vivo st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 209 publications
(314 reference statements)
4
20
0
Order By: Relevance
“…However, a study by Ibragic and Sofić found that E. foeminea had the lowest total phenolic content (TPC), and had among the lowest total alkaloids content (TAC) and total flavonoids content (TFC) compared to the other tested Ephedra species [ 5 ]. A diverse number of antioxidant terpenoids have also been identified in our study, some of which have been detected in E. sinica in a previous study by Qingbiao et al, such as β-ionone, cumin aldehyde, geranyl acetate, and p-cymene [ 67 ]. Other detected terpenoids with antioxidant potential included andrographolide and cafestol, both of which have yet to be reported in previous studies [ 68 , 69 ].…”
Section: Discussionsupporting
confidence: 62%
“…However, a study by Ibragic and Sofić found that E. foeminea had the lowest total phenolic content (TPC), and had among the lowest total alkaloids content (TAC) and total flavonoids content (TFC) compared to the other tested Ephedra species [ 5 ]. A diverse number of antioxidant terpenoids have also been identified in our study, some of which have been detected in E. sinica in a previous study by Qingbiao et al, such as β-ionone, cumin aldehyde, geranyl acetate, and p-cymene [ 67 ]. Other detected terpenoids with antioxidant potential included andrographolide and cafestol, both of which have yet to be reported in previous studies [ 68 , 69 ].…”
Section: Discussionsupporting
confidence: 62%
“…The in vitro anti-inflammatory validation exhibited good COX-2 inhibition activity of vitexin with an IC 50 value of 27.91 ± 1.74 µM. This result was in support of prior studies, which demonstrated the anti-inflammatory activity of vitexin via downregulation of pro-inflammatory cytokines releases, as well as reducing the actions of inflammatory mediators like COX-1 and COX-2 ( Babaei et al, 2020 ; Abdulai et al, 2021 ; Peng et al, 2021 ). Likewise, the moderate COX-2 inhibition of astragalin (IC 50: 49.05 ± 1.49 µM) contributed to the explanation of its multifaceted activity to mitigate inflammation.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have highlighted the relevance of vitexin in glucose homeostasis. It helps in the protection of pancreatic tissues from damage, enhances the uptake of glucose, and modulates the catalytic function of the two main digestive enzymes α-amylase and α-Glu ( He et al, 2016 ; Seyedan et al, 2019 ; Abdulai et al, 2021 ). In the same way, previous investigations have highlighted the hypoglycemic effectivities of astragalin through inhibition of key enzymes like α-Glu, α-amylase, and tyrosine phosphatase (PTP 1B) ( Cen et al, 2017 ; Lima et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…They were identified to be derivatives of apigenin and luteolin, including vitexin (apigenin-8-C-glucoside), isovitexin (apigenin-6-C-glucoside), orientin (luteolin-8-C-glucoside), isoorientin (luteolin-6-C-glucoside), luteolin-6-8-di-C-hexose, apigenin-6,8-di-C-hexose, apigenin-6-C-pentose-8-C-hexose, apigenin-6-C-hexose-8-Cpentose, luteolin-6-C-hexose-8-C-deoxyhexose, and apigenin-6-C-hexose-8-C-deoxyhexose (Figure 5) [21]. Vitexin, isovitexin, orientin, and isoorientin are mono-C-glycosylflavones with the anomeric carbon of their sugar moieties (β-D-glucopyranose) being bonded to either the C-8 or C-6 position of the flavone skeleton (apigenin and luteolin) through a carbon-carbon bond [35,36]. A higher concentration of these flavone-C-glycosides was found to be present in the extracts of the polar solvents as compared to those of the intermediate and non-polar solvents.…”
Section: Flavonesmentioning
confidence: 99%